Small signal modeling and stability analysis of multi-VSCs for grid-forming converters under low impedance grid - Yongkang CHEN; Yunhui HUANG; Zheng FANG; Dong WANG; Jinrui TANG; Keliang ZHOU (电力工程技术)
The grid-forming converter has voltage source characteristics，providing damping and frequency support to high-impedance weak grids，and demonstrates good stability. However，instability may occur under low impedance grids. This paper focuses on the small-signal modeling and stability analysis of multi-voltage source converters （VSCs） for grid-forming converters under low-impedance condition. Firstly，a small-signal model of multi-VSCs for grid-forming converters connected to the grid under low impedance is established，clarifying the system’s dynamic characteristics and coupling mechanism. Secondly，through eigenvalue trajectory and participation factor analysis，the dominant oscillation modes and their impact on system stability under different grid strengths and different control parameters are discussed. Finally，MATLAB time-domain simulations are conducted to verify the accuracy of the modeling and stability analysis results. The research results show that the increase in grid strength，reduction in active power，decrease in the droop coefficient，and reduction in interconnection impedance all weaken the stability of multi-VSCs for grid-forming converters，with the power loop and voltage loop being the dominant control loops affecting system stability.